2020
DOI: 10.1073/pnas.1911884117
|View full text |Cite
|
Sign up to set email alerts
|

Dinoflagellates with relic endosymbiont nuclei as models for elucidating organellogenesis

Abstract: Nucleomorphs are relic endosymbiont nuclei so far found only in two algal groups, cryptophytes and chlorarachniophytes, which have been studied to model the evolutionary process of integrating an endosymbiont alga into a host-governed plastid (organellogenesis). However, past studies suggest that DNA transfer from the endosymbiont to host nuclei had already ceased in both cryptophytes and chlorarachniophytes, implying that the organellogenesis at the genetic level has been completed in the two systems. Moreove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 90 publications
3
46
0
Order By: Relevance
“…On the other hand, a previous study on the nucleomorph genomes of both the lineages indicated that EGTs from the nucleomorphs were likely to have already ceased [4]. Recently, we reported two novel nucleomorph-bearing dinoflagellates for the first time in the last 30 years [7]. These two distantly related dinoflagellates, namely MGD and TGD strains, possess the green alga-derived compartment containing a relic nucleus and a plastid.…”
Section: Main Textmentioning
confidence: 88%
See 4 more Smart Citations
“…On the other hand, a previous study on the nucleomorph genomes of both the lineages indicated that EGTs from the nucleomorphs were likely to have already ceased [4]. Recently, we reported two novel nucleomorph-bearing dinoflagellates for the first time in the last 30 years [7]. These two distantly related dinoflagellates, namely MGD and TGD strains, possess the green alga-derived compartment containing a relic nucleus and a plastid.…”
Section: Main Textmentioning
confidence: 88%
“…Transcriptome analyses revealed that some photosynthesis-related proteins of green algal origin are encoded in both nuclear and nucleomorph genomes. This recent finding suggested that genome reorganization via EGTs in both TGD and MGD is still incomplete [7]. Phylogenetic analyses also indicated that the origins of both endosymbionts are close relatives of a particular green algal genus, Pedinomonas.…”
Section: Main Textmentioning
confidence: 98%
See 3 more Smart Citations